Floral Distribution and Diversity of Alien and Native Plants in Cebu Memorial Park, Cebu City, Philippines (Biosaintifika: Journal of Biology & Biology Education, 2022)
Metro Cebu, Philippines has a history of over 800 years of urbanization, making it a unique location for urban ecological studies. Urbanization can have a significant impact on floral communities, but the species composition and variety of urban cemeteries in Metro Cebu have not been reported. We calculated floral species richness (N), abundance (n), evenness (PE), and diversity (H' and D) by conducting the first floral survey (local plants and alien plants) in an urban cemetery in Metro Cebu. Subsequently, we evaluated the distribution pattern of floral species and the relationships between the richness of floral species and human activities. A total of 61 floral species (n=1,515) were recorded, with the proportion of APs (n=53; 86.88%) being much larger than the number of NPS (n=8; 13.11%). Shannon-Wiener Diversity index was calculated to be 2.69, Simpson's Diversity index was 0.16, and Pielou's Evenness was 0.65. Our research provides the first information on floral species in Metro Cebu, Philippines, and serves as a baseline for future studies and conservation efforts.